Strategi Pengelolaan Pariwisata Pinus Lahendong Di Kota Tomohon - Menajang, Sandy Andreo; Kalangi, John A. F.; Mukuan, Danny D. S. (Sam Ratulangi University, 2019)
The purpose of this research is to know the management strategies of tourism Pine Lahendong and know what are the factors that’s encourages and inhibit Pine Lahendong Tourism management strategies. The problem in this research is how Tourism Pinus Lahendong management strategies and what are the factors that inhibit and encourage Tourism Pinus Lahendong management strategies. Tourism is one of the things that are important to a country, the existence of this tourism, then a country or more specifically the Government of the region where it is tourist attraction, will get the infusion of revenues per tourist attractions. The marketing strategy is basically a thorough plan, integrated and fused in the marketing field, which gives guidelines on the activities that will be executed to achieve the marketing goals of a company. Tourism Pinus Lahendong strategy and potential for managed, developed and marketed because it has beautiful natural scenery and a sulfur hot springs into a visitor attraction. This research which means to understand the phenomenon or strengths, weaknesses, opportunities and threats from Tourism Pinus Lahendong holistically with described it in the form of words and language so as to produce a depiction on the phenomenon that happens. the results of the SWOT analysis conducted in the Tourism development of tourism policy, then Pinus Lahendong is improving promotion through various media, to improve the existing facilities in order to provide convenience for visitors and capitalize on potential at once elaborated the opportunities that can be sold and can attract visitors.